Impact of Implementation of Information Security Risk Management and Security Controls on Cyber Security Maturity (A Case Study at Data Management Applications of XYZ Institute) - Endro Joko Wibowo; Kalamullah Ramli (Jurnal Sistem Informasi, 2022)
Information security is an important concern for governments and industry due to the increase in cyber attacks during Covid-19. The government is obliged to maintain information security in implementing an Electronic-Based Government System following Presidential Regulation of the Republic of Indonesia Number 95 of 2018. To overcome this problem, the XYZ Institute needs an approach to implementing information security risk management and information security controls. This study aims to risk identification, risk analysis, risk evaluation, risk treatment, risk acceptance, risk control, and analysis of cyber security maturity gaps in the domain of governance, identification, protection, detection, and response. ISO/IEC 27005:2018 as guidance for conducting risk assessments. The code of practice for information security control uses the ISO/IEC 27002:2013 standard and assessing maturity using the cyber security maturity model version 1.10 developed by the National Cyber and Crypto Agency of the Republic of Indonesia. The results show that the cyber maturity value increased from 3.19 to 4.06 after implementing 12 new security controls.